Effects of Banana Resistant Starch on the Biochemical Indexes and Intestinal Flora of Obese Rats Induced by a High-Fat Diet and Their Correlation Analysis - Fu, Jinfeng; Wang, Yuting; Tan, Simin; Wang, Juan (Frontiers in Bioengineering and Biotechnology, 2021)
The effects of banana resistant starch (BRS) on obesity-related metabolic and intestinal flora were investigated in a high-fat diet-induced obesity model. After 6 weeks of intervention, the glucolipid metabolism index (blood glucose (GLU), total cholesterol (TC), triacylglycerol (TG), low density lipoprotein-cholesterol (LDL-C) and high density lipoprotein-cholesterol (HDL-C)), hormone index (leptin (LEP), insulin (INS), ghrelin, adiponectin (ADP) and thyroxine (T4)) and 16S rRNA sequencing analyses were performed for each group to explore the regulating effect of intestinal flora and the mechanism of weight loss in obese rats. The results showed that (1) BRS intervention significantly reduced the levels of GLU, TG, TC, LDL-C, LEP and INS (p<0.01) and increased the contents of ghrelin (p<0.05) and ADP (p<0.01). (2) BRS could improve the diversity of intestinal flora and regulate the overall structure of intestinal microorganisms, mainly by upregulating the Bacteroides/Firmicutes ratio and the relative abundance of Cyanobacteria and downregulating the relative abundances of Deferribacteres and Tenericutes (at the phylum level). BRS could inhibit the proliferation of Turicibacter, Romboutsia and Oilgella and increase the abundances of Bacteroides, Ruminococcaceae and Lachnospiraceae (at the genus level). (3) Some significant correlations were observed between the gut microbiota and biomarkers. Turicibacter, Romboutsia and Oligella were positively correlated with GLU, TG, TC, LEP and INS and negatively correlated with ghrelin and ADP. Bacteroides, Parabacteroides, and Akkermansia were negatively correlated with GLU, TG and TC. Conclusion: BRS had promising eﬀects on weight loss, which could be associated with the improvement in host metabolism by regulating intestinal flora.